Corporate Social Responsibility as a Public Policy Innovation: Bridging Business and Governance for Sustainable Development - Cristyano, Cristyano; Suryadi, Suryadi; Riyanto, Riyanto (Department of Public Administration, 2025)
Corporate Social Responsibility (CSR) has increasingly emerged as a critical innovation in public policy, serving as a bridge between the business sector and government governance to advance sustainable development. This study examines CSR as a strategic tool for creating public value through multi-stakeholder collaboration, integrating corporate initiatives with public policy objectives. Employing a systematic review of recent literature, the research highlights how CSR adoption enhances transparency, accountability, and effectiveness in addressing social and environmental challenges. The findings reveal that CSR practices contribute significantly to improving corporate social accountability while strengthening the relationship between businesses and governments in achieving the Sustainable Development Goals (SDGs). Moreover, CSR initiatives encourage the development of inclusive policies that foster cooperation across sectors and promote innovation in addressing complex societal issues. The study underscores the importance of adaptive and context-sensitive CSR implementation to ensure that both corporate and public interests are aligned. Practical recommendations are provided for policymakers and business leaders to develop frameworks that support the integration of CSR within public governance structures. By facilitating collaborative governance and stakeholder engagement, CSR emerges as a transformative approach that not only advances corporate responsibility but also catalyzes systemic change toward social equity and environmental sustainability. This research contributes to a deeper understanding of CSR’s role in public policy innovation and offers valuable insights for fostering sustainable partnerships between the private and public sectors.